Slow-release functional material and preparation method thereof

By extruding or mixing the water-soluble phase and the non-water-soluble phase at 80 to 170°C, a slow-release functional material with a co-continuous structure is formed, which solves the problem of low release rate of functional substances and achieves stable and slow release of functional ingredients. Suitable for a variety of functional ingredients.

CN119331324APending Publication Date: 2025-01-21WUXI LITTLE SWAN ELECTRIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310887888.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, it is difficult for functional substances to form stable release paths in carriers, resulting in low release rate and inability to fully exert the role of functional substances.

Method used

By squeezing out or densely mixed with the water -soluble phase and non -water -soluble phase ingredients at 80 ~ 170 ° C to form a sustained -release functional material with a consecutive continuous structure, the particle size of the water -soluble phase particles is within the range of 100nm to 10 μm, and the functional ingredients can be achieved. Slowly release.

Benefits of technology

The stable release of functional ingredients is achieved, the release rate is controlled at 0.0001 ~ 0.0033g/L. It is suitable for functional components such as Jiuyanjia base, polychen Liuya, ammonium salt, sulfuric acid, amino acids and other types of functional ingredients. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331324A_ABST
    Figure CN119331324A_ABST
Patent Text Reader

Abstract

The invention relates to a slow-release functional material and a preparation method thereof. The invention relates to a preparation method of a slow-release functional material, which adopts a one-step method or a two-step method. The one-step method comprises the following steps: carrying out extrusion blending or banburying blending on the non-water-soluble phase, the water-soluble matrix and the functional component, and granulating to obtain the slow-release functional material; the operation temperature of extrusion blending or internal mixing blending is 80-170 DEG C; the two-step method comprises the following steps: blending the water-soluble matrix and the functional components for the first time, and granulating to obtain water-soluble master batch; blending the water-soluble master batch and the non-water-soluble phase for the second time, and granulating to obtain a slow-release functional material; both the first blending and the second blending adopt extrusion blending or internal mixing blending, and the operation temperature is 80-170 DEG C. The problem that the total release amount of functional molecules is low is solved, and the slow release effect can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of materials, and in particular to a sustained-release functional material and a preparation method thereof. Background Art

[0002] In the field of cleaning, the current way to achieve multiple functions such as deodorization, descaling, and sterilization is usually to add functional substances to the working environment, such as aromatherapy for deodorization, salts for descaling, silver phosphates for sterilization, guanidines for long-term antibacterial effects, and healthy natural sterilization. In order to facilitate use and maintain the long-term effectiveness of the functional effects, the above-mentioned functional substances usually need to be loaded in a carrier, such as silver phosphate needs to be loaded in glass, natural antibacterial agents and guanidines need to be loaded in a plastic matrix, and activated carbon that can load descaling salts can be loaded. However, in essence, the above-mentioned functional substances are mostly inorganic substances or small molecules, which are basically randomly dispersed in the matrix, and it is difficult to form a stable release path. Therefore, in theory, only the functional substances dispersed on the surface can be released and play a functional role, but the functional substances inside the matrix are difficult to dissolve in water and release, and the role of the functional substances cannot be fully exerted.

[0003] To this end, the present invention is proposed. Summary of the invention

[0004] The purpose of the present invention is to provide a sustained-release functional material and a preparation method thereof, which solves the problem of low release rate of functional substances and inability to sustain release.

[0005] In order to achieve the above objectives, the present invention provides the following technical solutions.

[0006] The first aspect of the present invention provides a sustained-release functional material, comprising a co-continuous structure formed by a water-soluble phase and a non-water-soluble phase; the water-soluble phase comprises a water-soluble matrix and a functional component;

[0007] The particle size of the water-soluble phase particles in the co-continuous structure is 100 nm to 10 μm.

[0008] Therefore, the present invention can control the release rate within the range of 0.0001 to 0.0033 g / L by controlling the particle size of the water-soluble phase particles in the sustained-release functional material within the range of 100 nm to 10 μm, and is therefore applicable to functional ingredients such as polyhexamethylene guanidine, polyhexamethylene biguanide, polyquaternary ammonium salts, calcium sulfite, and amino acids.

[0009] Preferably, the release rate of the functional ingredient reaches: 0.0001-0.0033 g / L.

[0010] In the present invention, the test method for the release rate is: prepare the sustained-release carrier material into a sample of 10mm×10mm×4mm with a mass of m1, rinse it with tap water at a flow rate of 2.5L / min, take out and dry the sample after the mass is constant, weigh it, and the mass is m2. The volume of water used for rinsing is v, and the dissolution rate = (m1-m2) / v.

[0011] The second aspect of the present invention provides a method for preparing the sustained-release functional material of the first aspect, which adopts a one-step method or a two-step method;

[0012] The one-step method comprises: extruding and blending the non-water-soluble phase, the water-soluble matrix and the functional component or mixing and blending, and granulating to obtain a sustained-release functional material; the operating temperature of the extrusion and mixing or mixing and blending is 80 to 170° C.;

[0013] The two-step method comprises: firstly, a water-soluble matrix and a functional component are blended for the first time, granulated to obtain a water-soluble masterbatch; then, the water-soluble masterbatch and a non-water-soluble phase are blended for the second time, granulated to obtain a sustained-release functional material; the first blending and the second blending are both performed by extrusion blending or banbury blending, and the operating temperature is 80 to 170°C.

[0014] In the present invention, different phases are evenly dispersed by one-step or two-step blending, and the blending temperature is controlled within 80 to 170° C., so that a co-continuous structure with a specific dispersion size can be formed. When the slow-release functional material prepared in this way is used in a water environment such as cleaning, a dissolution channel will be formed in the non-aqueous phase along with the dissolution release of the water-soluble matrix, so that all functional components are slowly released into water at a suitable rate along with the water-soluble matrix, and their functions are exerted until they are substantially completely dissolved. Since the slow-release functional material has a specific dispersion size due to process adjustment, the release rate can be controlled within 0.0001 to 0.0033 g / L, and therefore it can be applied to functional components of types such as polyhexamethylene guanidine, polyhexamethylene biguanide, polyquaternary ammonium salt, calcium sulfite, and amino acids.

[0015] On this basis, the distribution of the water-soluble matrix in the co-continuous structure (including size, volume proportion, etc.) can be further adjusted by adjusting the blending time, rotation speed, annealing conditions, etc., thereby adjusting the release channel characteristics of the functional components to regulate the sustained release life, etc., as listed below.

[0016] Preferably, the one-step method adopts extrusion blending, and the extrusion blending time is 4 to 10 minutes;

[0017] Alternatively, the one-step method adopts banburying and blending, and the banburying and blending time is 10 to 30 minutes.

[0018] Preferably, in the two-step method, the first blending and the second blending are both performed by extrusion blending, and the extrusion blending time for each time is 2 to 5 minutes;

[0019] Alternatively, the first blending and the second blending are both performed by banburying, and the time for each banburying is 5 to 15 minutes.

[0020] Preferably, the one-step method and the two-step method adopt extrusion blending, and the screw speed of the extrusion blending is 30 to 150 rpm;

[0021] Alternatively, when the one-step method and the two-step method adopt internal kneading and blending, the rotor speed of the internal kneading and blending is 30 to 150 rpm.

[0022] Preferably, the method further comprises: subjecting the sustained-release functional material to an annealing treatment at 50-70° C. for more than 6 hours.

[0023] Preferably, the annealing treatment comprises: treating at 60-70° C. for 6-8 hours.

[0024] Preferably, the non-aqueous phase comprises at least one of the following: POE, EVA, PBAT, PCL, PLA, PBS, PE, PP, PS, ABS;

[0025] The water-soluble matrix includes at least one of the following: PVA, PEG, PEO, polyacrylamide;

[0026] The functional components preferably include at least one of a bactericide, a water softener, a descaling agent, and a color fixing agent.

[0027] In addition, for specific types of functional ingredients such as fungicides, the present invention provides a more preferred combination of water-soluble phase and water-insoluble phase, as well as a more matched blending method and conditions thereof, as described below.

[0028] Preferably, the water-soluble phase matrix includes PEO, the non-water-soluble phase includes at least one of PE and PP, and the functional molecule includes a bactericide;

[0029] The two-step method is adopted for preparation, the first blending and the second blending are both extrusion blending, each extrusion blending is carried out in a twin-screw extruder, and the working conditions of each extrusion blending include: the temperature of the first zone is 70-90°C, the temperature of the second zone is 110-140°C, the temperature of the third zone is 140-170°C, the temperature of the fourth zone is 140-170°C, the temperature of the fifth zone is 140-170°C, the temperature of the sixth zone is 140-170°C, and the die temperature is 120-130°C.

[0030] Preferably, the working conditions for each extrusion blending include: zone one temperature of 80-90°C, zone two temperature of 110-140°C, zone three temperature of 140-170°C, zone four temperature of 140-170°C, zone five temperature of 140-170°C, zone six temperature of 140-170°C, and die temperature of 120-130°C.

[0031] Preferably, the functional ingredients include at least one of a bactericide, a water softener, a descaling agent, and a color fixing agent.

[0032] Preferably, the fungicide includes at least one of the following: monoguanidine fungicides, biguanide fungicides, amino acid fungicides, quaternary ammonium salt fungicides, metal fungicides, metal oxide fungicides, polyphenol fungicides, pyridine fungicides, and plant extract fungicides;

[0033] In summary, compared with the prior art, the present invention achieves the following technical effects:

[0034] (1) The water-soluble phase and the water-insoluble phase components are extruded or kneaded at 80-170° C. to obtain a sustained-release material. The material has a co-continuous structure and has the advantages of sustained release and high release rate. It is suitable for functional components with lower release amounts. The release rate of the sustained-release material in water can be controlled at: 0.0001-0.0033 g / L.

[0035] (2) Optimize the sustained release effect by further optimizing the blending time, rotation speed, annealing conditions, etc.

[0036] (3) By adopting appropriate extrusion blending conditions, the dissolution rate of specific functional ingredients such as bactericides can be accurately controlled or the stability of sustained-release materials can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0038] Figure 1 The figure is a schematic diagram of the microstructure of a sustained-release material of the present invention. DETAILED DESCRIPTION

[0039] The embodiments of the present invention will be described in detail below in conjunction with examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. The original drugs, reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be purchased commercially or can be prepared according to the prior art.

[0040] The chemical substances involved in the present invention are defined as follows.

[0041] POE: Polyolefin elastomer.

[0042] EVA: Ethylene-vinyl acetate copolymer.

[0043] PBAT: poly(butylene terephthalate-adipate).

[0044] PCL: poly-ε-caprolactone.

[0045] PLA: Polylactic acid.

[0046] PBS: polybutylene succinate.

[0047] PE: Polyethylene.

[0048] PP: Polypropylene.

[0049] PS: Polystyrene.

[0050] ABS: Acrylonitrile butadiene styrene plastic.

[0051] PVA: polyvinyl alcohol.

[0052] PEG: polyethylene glycol.

[0053] PEO: Polyethylene oxide.

[0054] In existing water-based cleaning or care products, the carriers for loading functional ingredients have no sustained-release effect, and the total release amount of the functional ingredients is low.

[0055] In order to solve the above technical problems, the present invention provides a method for preparing a sustained-release functional material, which adopts a one-step method or a two-step method;

[0056] The one-step method comprises: extruding and blending the non-water-soluble phase, the water-soluble matrix and the functional component or mixing and blending, and granulating to obtain a sustained-release functional material; the operating temperature of the extrusion and mixing or mixing and blending is 80 to 170°C;

[0057] The two-step method includes: firstly, the water-soluble matrix and the functional components are blended for the first time, granulated to obtain the water-soluble masterbatch; then the water-soluble masterbatch and the non-water-soluble phase are blended for the second time, granulated to obtain the sustained-release functional material; the first blending and the second blending are both performed by extrusion blending or banbury blending, and the operating temperature is 80-170°C.

[0058] In the present invention, different phases are evenly dispersed by one-step or two-step blending, and the blending temperature is controlled within 80 to 170° C., so that a co-continuous structure with a specific dispersion size can be formed. When the slow-release functional material prepared in this way is used in a water environment such as cleaning, a dissolution channel will be formed in the non-aqueous phase along with the dissolution release of the water-soluble matrix, so that all functional components are slowly released into water at a suitable rate along with the water-soluble matrix, and their functions are exerted until they are basically completely dissolved. Since the slow-release functional material has a specific dispersion size due to process adjustment, the particle size of the water-soluble phase particles dispersed in the non-aqueous phase is 100nm to 10μm, and its release rate in water can be controlled within 0.0001 to 0.0033g / L, so it can be applied to functional components such as polyhexamethylene guanidine, polyhexamethylene biguanide, polyquaternary ammonium salt, calcium sulfite, and amino acids.

[0059] The co-continuous structure of the present invention is a three-dimensional network structure constructed by blending a water-soluble phase and a non-water-soluble phase. Figure 1 In the microstructure shown, the gray area is the matrix formed by the non-aqueous phase, and the white area is the water-soluble phase. The water-soluble phase can be evenly dispersed in the non-aqueous phase, and the water-soluble phase of the present invention covers the functional components. Therefore, when the sustained-release functional material with such a structure contacts water, the water-soluble phase will continuously dissolve in water, thereby continuously releasing the functional components.

[0060] The water-soluble phase particles of the present invention refer to particles dispersed by a non-aqueous phase, that is, water-soluble phase particles dispersed in a non-aqueous phase.

[0061] The functional components coated by the above sustained-release functional materials can be arbitrary, including but not limited to agents for cleaning or caring for clothes, and can also be agents for purifying water, etc.

[0062] In some embodiments, the release rate of the above sustained-release functional materials in water can be controlled within 0.002 to 0.0033 g / L.

[0063] In some embodiments, the functional ingredient includes at least one of a bactericide, a water softener, a descaling agent, and a color fixing agent.

[0064] In some embodiments, the fungicide includes at least one of the following: monoguanidine fungicides, biguanide fungicides, amino acid fungicides, quaternary ammonium salt fungicides, metal fungicides, metal oxide fungicides, polyphenol fungicides, pyridine fungicides, and plant extract fungicides.

[0065] In some embodiments, the water softener includes at least one of the following: phosphates, silicates, imide sulfonates, amino acid derivatives, hydroxy acids and their derivatives, polyacrylic acid and their derivatives.

[0066] In some embodiments, the descaling agent includes at least one of: sodium citrate, disodium EDTA.

[0067] In some embodiments, the color fixing agent includes at least one of the following: polyhexamethylene guanidine, polyhexamethylene biguanide, polyquaternium salt. In the present invention, the selection and matching of the non-aqueous phase and the aqueous phase components are arbitrary. For example, the non-aqueous phase includes but is not limited to at least one of the following: POE, EVA, PBAT, PCL, PLA, PBS, PE, PP, PS, ABS;

[0068] The water-soluble matrix includes, but is not limited to, at least one of the following: PVA, PEG, PEO, polyacrylamide.

[0069] The combination of the two includes but is not limited to the following table.

[0070] Table 1

[0071] Non-aqueous phase Water soluble matrix PBAT PVA PCL PEG PLA PEO PBS Polyacrylamide PE PVA PP PEG ABS PEO PS Polyacrylamide

[0072] On the basis of the above, the distribution (including size, volume proportion, etc.) of the water-soluble matrix in the co-continuous structure can be further adjusted by adjusting the blending time, rotation speed, annealing conditions, etc., thereby adjusting the release channel characteristics of the functional components to regulate the sustained release life, etc., as listed below.

[0073] In some embodiments, the one-step method uses extrusion blending, and the extrusion blending time is 4 to 10 minutes.

[0074] In some embodiments, the one-step method uses internal mixing and the internal mixing time is 10 to 30 minutes.

[0075] When the blending time of the two phases is controlled within the above range, the two-phase materials can be sheared to an appropriate degree to form a sustained-release functional material with a water-soluble phase particle size in the range of 100 nm to 10 μm.

[0076] In some embodiments, in the two-step method, both the first blending and the second blending are performed by extrusion blending, and the extrusion blending time for each time is 2 to 5 minutes.

[0077] In some embodiments, both the first blending and the second blending are performed by internal mixing, and the internal mixing time of each blending is 5 to 15 minutes.

[0078] Compared with the one-step method, the two-step method has a better sustained release effect, which can make more functional components be encapsulated in the water-soluble phase, thereby avoiding the slow-release functional material from releasing a large amount of functional components in the initial stage of dissolving in water, resulting in a shortened material life. On this basis, by controlling the time of each blending within the above range, the particle size of the water-soluble phase particles can be within the range of 100nm to 10μm.

[0079] In some embodiments, the one-step method and the two-step method use extrusion blending, and the screw speed of the extrusion blending is 30-150 rpm.

[0080] In some embodiments, when the one-step method and the two-step method adopt internal mixing and blending, the rotor speed of the internal mixing and blending is 30-150 rpm.

[0081] Since the water-soluble phase particles obtained in the present invention have a small particle size, they are prone to agglomeration and other problems. At this time, controlling the rotation speed of extrusion blending and internal mixing blending within the above range can reduce the agglomeration problem and make the two phases more evenly dispersed.

[0082] In some embodiments, it also includes: annealing the sustained-release functional material at 50-70°C for more than 6 hours.

[0083] Annealing can improve the particle appearance and release uniformity, and accelerate the release rate. The main principle is that after annealing, the surface burrs disappear and the particles become more rounded. In addition, non-water-soluble polymer materials and water-soluble polymer materials will aggregate, making the microstructure more uniform.

[0084] In some embodiments, the annealing treatment is preferably performed at 60-70° C. for 6-8 hours.

[0085] The present invention also provides preferred preparation conditions for a sustained-release functional material taking a bactericide as an example.

[0086] Specifically, in some embodiments, the water-soluble phase includes PEO, the water-insoluble phase includes at least one of PE and PP, and the functional molecule includes a fungicide;

[0087] And preferably adopt two-step preparation, the first blending and the second blending are both extrusion blending, each extrusion blending is carried out in a twin-screw extruder, and the working conditions of each extrusion blending include: the temperature of zone 1 is 70-90°C, the temperature of zone 2 is 110-140°C, the temperature of zone 3 is 140-170°C, the temperature of zone 4 is 140-170°C, the temperature of zone 5 is 140-170°C, the temperature of zone 6 is 140-170°C, and the die temperature is 120-130°C.

[0088] Such processing conditions can enable the fungicide to achieve a good sustained-release effect, specifically: the fungicide is basically dispersed in the water-soluble polymer, and the fungicide can be basically completely released.

[0089] Furthermore, the working conditions of each extrusion blending include: zone 1 temperature of 80-90°C, zone 2 temperature of 110-140°C, zone 3 temperature of 140-170°C, zone 4 temperature of 140-170°C, zone 5 temperature of 140-170°C, zone 6 temperature of 140-170°C, and die temperature of 120-130°C.

[0090] The present invention also provides the following embodiments.

[0091] Example 1

[0092] Sustained-release functional materials with bactericidal effect

[0093] Take PEO, polyhexamethyleneguanidine PHMG, and low-density polyethylene and prepare them according to the following steps.

[0094] (1) PEO (molecular weight 300,000) was dried at 50°C for 6 hours;

[0095] (2) using a twin-screw extruder, PEO and polyhexamethylene guanidine PHMG are first blended in a mass ratio of 2:1, the operating temperature of the twin-screw extruder is: the temperature of zone 1 is 80°C, the temperature of zone 2 is 120°C, the temperature of zone 3 is 140°C, the temperature of zone 4 is 140°C, the temperature of zone 5 is 140°C, the temperature of zone 6 is 140°C, and the die temperature is 120°C; the screw speed is 50 rpm, and the material residence time is 3 min;

[0096] The mixture obtained by the first blending is air-cooled to below 50° C., and then granulated to obtain a water-soluble masterbatch with a particle size of 2-5 mm;

[0097] (3) using a twin-screw extruder, the water-soluble masterbatch obtained in step (2) and low-density polyethylene (Maoming Petrochemical low-density polyethylene 2426H, number average molecular weight 90,000) are blended for the second time at a mass ratio of 55:45, the operating temperature of the twin-screw extruder is: the temperature of zone 1 is 80°C, the temperature of zone 2 is 140°C, the temperature of zone 3 is 170°C, the temperature of zone 4 is 170°C, the temperature of zone 5 is 170°C, the temperature of zone 6 is 170°C, and the die temperature is 160°C; the screw speed is 50 rpm, and the material residence time is 3 min;

[0098] The mixture obtained by the second blending is air-cooled to below 50° C., and then granulated to obtain a sustained-release antibacterial material.

[0099] Example 2

[0100] The difference from Example 1 is that the functional components are different, polyhexamethylene guanidine PHMG is replaced by calcium sulfite, and the other conditions are the same as Example 1.

[0101] Example 3

[0102] The difference from Example 1 is that the conditions for the two extrusion blending are different, as shown in Table 2, and the other conditions are the same as Example 1.

[0103] Example 4

[0104] The difference from Example 1 is that the blending is completed in one step:

[0105] All raw materials were blended by a twin-screw extruder. The working temperature of the twin-screw extruder was: 80°C in zone 1, 120°C in zone 2, 140°C in zone 3, 140°C in zone 4, 140°C in zone 5, 140°C in zone 6, and a die temperature of 120°C. The screw speed was 50 rpm, and the material residence time was 6 min.

[0106] The blended mixture is air-cooled to below 50° C. and then granulated to obtain a sustained-release functional material.

[0107] The remaining conditions are the same as in Example 1.

[0108] Examples 5 to 7

[0109] The difference from Example 1 is that after step (3), the obtained particles are further annealed. The annealing conditions are shown in Table 2.

[0110] Comparative Example 1

[0111] The difference from Example 1 is that the conditions for the two extrusion blending are different, as shown in Table 2, and the other conditions are the same as Example 1.

[0112] The sustained-release properties of the materials of the above embodiments and control examples in water were tested, and the results are shown in Table 2.

[0113] The test method for the release rate is as follows: prepare the sustained-release carrier material into a sample of 10mm×10mm×4mm with a mass of m1, and rinse it with tap water at a flow rate of 2.5L / min. After the sample mass becomes constant, take it out and dry it, and weigh it with a mass of m2. The volume of water used for rinsing is v, and the dissolution rate = (m1-m2) / v.

[0114] Table 2

[0115]

[0116]

[0117] The above data show that the type of non-aqueous phase, the type of water-soluble matrix and the ratio of the two have a significant impact on the sustained-release effect.

[0118] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A sustained-release functional material, characterized in that: A co-continuous structure comprising a water-soluble phase and a non-water-soluble phase; the water-soluble phase comprises a water-soluble matrix and functional components; The particle size of the water-soluble phase particles in the co-continuous structure is 100 nm to 10 μm.

2. The sustained-release functional material according to claim 1, characterized in that: The sustained-release functional material is in water, and the release rate of the functional component reaches: 0.0001-0.0033 g / L.

3. The method for preparing the sustained-release functional material according to any one of claims 1 to 2, characterized in that: Use a one-step or two-step approach; The one-step method comprises: extruding and blending the non-water-soluble phase, the water-soluble matrix and the functional component or mixing and blending, and granulating to obtain a sustained-release functional material; the operating temperature of the extrusion and mixing or mixing and blending is 80 to 170° C.; The two-step method comprises: firstly, a water-soluble matrix and a functional component are blended for the first time, granulated to obtain a water-soluble masterbatch; then, the water-soluble masterbatch and a non-water-soluble phase are blended for the second time, granulated to obtain a sustained-release functional material; the first blending and the second blending are both performed by extrusion blending or banbury blending, and the operating temperature is 80 to 170°C.

4. The preparation method according to claim 3, characterized in that: The one-step method adopts extrusion blending, and the extrusion blending time is 4 to 10 minutes; Alternatively, the one-step method adopts banburying and blending, and the banburying and blending time is 10 to 30 minutes.

5. The preparation method according to claim 3, characterized in that: In the two-step method, the first blending and the second blending are both performed by extrusion blending, and the extrusion blending time for each time is 2 to 5 minutes; Alternatively, both the first blending and the second blending are performed by banburying, and the time of each banburying blending is 5 to 15 minutes.

6. The preparation method according to claim 3, characterized in that: The one-step method and the two-step method use extrusion blending, and the screw speed of the extrusion blending is 30 to 150 rpm; Alternatively, the one-step method and the two-step method adopt internal kneading and blending, and the rotor speed of the internal kneading and blending is 30-150 rpm.

7. The preparation method according to any one of claims 3 to 6, characterized in that: Also includes: Annealing the sustained-release functional material at 50-70° C. for more than 6 hours; Preferably, the annealing treatment comprises: treating at 60-70° C. for 6-8 hours.

8. The preparation method according to claim 3, characterized in that: The non-aqueous phase includes at least one of the following: POE, EVA, PBAT, PCL, PLA, PBS, PE, PP, PS, ABS; The water-soluble matrix includes at least one of the following: PVA, PEG, PEO, polyacrylamide; The functional components preferably include at least one of a bactericide, a water softener, a descaling agent, and a color fixing agent.

9. The preparation method according to claim 8, characterized in that: The water-soluble phase matrix includes PEO, the non-water-soluble phase includes at least one of PE and PP, and the functional molecule includes a bactericide; Preferably, the two-step method is adopted for preparation, the first blending and the second blending are both extrusion blending, each extrusion blending is carried out in a twin-screw extruder, and the working conditions of each extrusion blending include: the temperature of zone 1 is 70-90°C, the temperature of zone 2 is 110-140°C, the temperature of zone 3 is 140-170°C, the temperature of zone 4 is 140-170°C, the temperature of zone 5 is 140-170°C, the temperature of zone 6 is 140-170°C, and the die temperature is 120-130°C.

10. The preparation method according to claim 9, characterized in that: The working conditions for each extrusion blending include: zone 1 temperature 80-90°C, zone 2 temperature 110-140°C, zone 3 temperature 140-170°C, zone 4 temperature 140-170°C, zone 5 temperature 140-170°C, zone 6 temperature 140-170°C, and die temperature 120-130°C.